2022
DOI: 10.3389/fevo.2022.983401
|View full text |Cite
|
Sign up to set email alerts
|

Urban green roofs can support a diversity of parasitoid wasps

Abstract: Green roofs are often installed atop buildings to provide ecological services such as mitigating storm water runoff and cooling air within urban heat islands. We found that green roofs in Portland, Oregon, also can support biodiversity, including a diverse assemblage of parasitoid wasps, with 20 morphospecies from 10 families present on the four roofs we surveyed. The roofs with greater plant diversity and structural complexity harbored comparatively more parasitoid morphospecies than the structurally simpler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
1
0
0
Order By: Relevance
“…Although we found almost 70% more hover ies than bees at our green roof sites. Similar to our study, green roofs have also been shown to support biocontrol agents such as parasitoid wasps (Diethelm and Masta, 2022), and predators and parasitoids in general (Fabián et al, 2021;Sánchez Domínguez et al, 2020). Contrary to our expectations, SE and BE green roofs had similar biodiversity metrics for bene cial insects, and there was a greater abundance of pollinators and natural enemies on SE green roofs.…”
Section: Discussionsupporting
confidence: 68%
“…Although we found almost 70% more hover ies than bees at our green roof sites. Similar to our study, green roofs have also been shown to support biocontrol agents such as parasitoid wasps (Diethelm and Masta, 2022), and predators and parasitoids in general (Fabián et al, 2021;Sánchez Domínguez et al, 2020). Contrary to our expectations, SE and BE green roofs had similar biodiversity metrics for bene cial insects, and there was a greater abundance of pollinators and natural enemies on SE green roofs.…”
Section: Discussionsupporting
confidence: 68%